Biomarker Research of Preclinical Alzheimer’s Disease and MCI Based on Neuroimage Techniques - Wu, Xia; Guo, Xiaojuan; Lai, Youzhi; Chen, Kewei; Yao, Li (Neuroscience and Biomedical Engineering (Discontinued), 2013)
Alzheimer’s disease (AD) is an aging-related and progressive neurodegenerative disease related with age. At the time of clinical manifestation of dementia AD, significant irreversible brain damage is already present, rendering the diagnosis of AD at early stages of the disease an urgent prerequisite for therapeutic treatment to halt, or at least slow, the onset or progression of the disease progression. Recent numerous studies using the state-of-art neuroimaging techniques that have identified AD-like structural and functional brain changes in elderly people who are cognitively within the normal range or who have mild cognitive impairment (MCI), a prodromal stage of the disease are discussed. In this review, we discussed various neuroimaging measures that are proving to have potential values as biomarkers of preclinical AD pathology for the its early detection and prediction as well as serving as a clinical trial outcome measures with additional validations.
Keywords: clinical trial